Injury prevention in artistic gymnastic: A guide for coaches and directions for research - Cossens, P. (ISBS - Conference Proceedings Archive (Konstanz), 2012)
Competitive artistic gymnastics is a high risk activity. Injury prevention essentials include: Avoid the `lumbar fold` into extension; Maximise hip extension range; Maximise thoracic extension range; Maximise thoracic rotation range; Gain calf strength and endurance; Ankle proprioceptive training. Injury prevention essentials may be important for all gymnastics coaches to recognise, but could also be used to guide future research investigating injuries in gymnastics.